Hubungan Tingkat Pengetahuan dan Sikap Kesehatan Reproduksi Remaja dengan Triad KRR pada Siswa MA Mafatihul Huda Padaherang Pengandaran - Atmarina Yuliani, Diah; Nuroctaviani, Putri (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
Adolescence is a period of transition, a period of searching for identity, with the flow of globalization and information that is getting out of control, youth can be called a transition season which is very rapid, both physically, psychologically and socially. With the inclusion of various information that is free, not through a filter that is correct according to ethics and normality, it can cause adolescents to be very vulnerable to harmful influences. This situation is exacerbated by the lack of concern for the family and society, and the community even considers it taboo to talk about reproductive issues. The consequences of this change are often associated with stereotypes (prejudice) regarding irregularities and irregularities. This type of research uses a quantitative correlation method using a cross-sectional approach with a total of 47 young female and male respondents. Retrieval of data using random sampling with analysis of the chi-squer test The results of this study show that the characteristics of adolescents (age and sex) are 48.9% female and 51.1% male, the level of knowledge is mostly included in the category of having sufficient knowledge 76.6%, less is 12.8%, most of the attitudes of the respondents negative 76.6%, most of which are included in the KRR triad are not good 66.0%. There is a relationship between the level of knowledge of adolescent reproductive health and the RH Triad with a p-value = 0.004 and there is a relationship between adolescent reproductive health attitudes and the KRR triad with a p-value = 0.001.